Field screening of cassava (Manihot esculenta Crantz) germplasm for desirable traits by the use of augmented design - Asante, I.K.; Dixon, Alfred G.O. (African Journals Online, 2006)
Ninety-eight cassava accessions were grown in augmented randomized complete block design to screen for superior clones with desirable traits. The desirable traits were root number (RTNO), fresh root yield (FYLD), harvest index (HI), dry matter (DM), cyanide potential (CNP), mean plant height (MPHT) and level of branching (LOBR). Three standard varieties were used, namely 30572, 91/01730 and 91/023227. Acessions that were superior to the standard types in more than one trait were 92/0681, 92/02325; 92/0455, 88/02555; Alice Local and 88/02555. These accessions could be selected and put into crossing blocks to combine the traits into one genotype. The present results show that augmented designs are efficient in the identification of superior cassava genotypes with desirable traits.